METHODOLOGY OF ETHICAL AND PHILOSOPHICAL RESEARCH OF THE ALTRUIST CONCEPTS IN MODERN SOCIAL THEORY - Humeniuk, Julia (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. Against the background of information tension and ideological discomfort, there are challenges related to the problems of life, preservation and development of personality, and humanistic culture. The search for new ways of civilizational development actualizes the search for an adequate methodology for ethical and philosophical research of altruism. Research methods are methods of theoretical research, analysis, and synthesis; methods of terminological analysis of concepts (definitions) of the components of scientific apparatus and the basic terms of scientific theme. The aim and tasks are the definition and analysis of the basic concepts, methods, and methodologies, the main stages of ethical and philosophical research of the concepts of altruism.. Research results. The article analyzes the concepts of "methodology", and "method" and names the main means of knowledge used in philosophy for further understanding and conscious application in the process of ethical and philosophical research of the concepts of altruism. Ethical and philosophical research of the concepts of altruism requires a description, analysis, and clarification of a number of concepts, the main of which at this stage are "altruism", "concept" and "theory". Discussion. The comprehensive ethical and philosophical study of the concepts of altruism is possible through the study of the history of the formation of ideas about altruism as a mode of human existence; revealing the nature of the manifestations of the diversity of dimensions of altruism in the modern social context; critical analysis of the concepts of altruism that have developed in the natural, social and behavioral sciences and in philosophy; development of a base of recommendations for the development of altruistic traits and intentions of the individual (in adulthood and maturity). The ethical and philosophical study of the concepts of altruism will be productive interdisciplinary integration of ethical-theoretical and ethical-applied, biologization, psychological, economic approaches; comparative, hermeneutic, anthropological methods of scientific knowledge. Comprehensive ethical and philosophical research may include the following stages: analysis of the theoretical and methodological foundations of the study of the concepts of altruism; identifying the features of the socio-biological dimension of altruism (R. Dawkins, M. Ridley, D. Swaab); clarifying the essence of the socio-psychological dimension of altruism (R. Frank, D. Goleman, S. Kaufman, V. Murty); defining the constructive socio-economic dimension of altruism (A. Grant, R. Thaler, D. Arieli). Generalization of the sociophilosophical (socio-cultural, ethical) dimension of altruism (Aristotle, D. Hume, A. Smith, P. Singer, W. Macascill) will reveal the development of altruistic qualities and intentions of personality in adulthood and maturity, which will provide opportunities for learning and adulthood education. Conclusions. Given the need to reflect on the methodology of scientific knowledge through its rapid and spiral development, the analysis was carried out and the basic concepts of scientific research were identified, which allowed to define the scientific apparatus and outline the main stages of this study. Using the method of terminological analysis of the definitions of "altruism", "concept", "theory" and understanding of their essence, the prospect of the ethical and philosophical study of concepts of altruism is associated with a comprehensive analysis of the moral principle of selfless service to othe